2006
DOI: 10.1111/j.0902-4441.2006.t01-1-ejh2783.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of thalidomide in refractory and relapsed multiple myeloma with emphasis on response duration

Abstract: These results show that the effect of thalidomide in refractory/relapsed MM can be sustained, particularly in patients who achieve a greater degree of response, and support the finding that this drug can be used for maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The 2-year event-free (EFS) and overall survival (OS) were 20% and 48%, respectively. [9][10][11] A systematic review of phase 2 trials identified 42 trials investigating 1674 patients. The PR rate was 29.4%.…”
Section: Clinical Experiences Single-agent Thalidomidementioning
confidence: 99%
“…The 2-year event-free (EFS) and overall survival (OS) were 20% and 48%, respectively. [9][10][11] A systematic review of phase 2 trials identified 42 trials investigating 1674 patients. The PR rate was 29.4%.…”
Section: Clinical Experiences Single-agent Thalidomidementioning
confidence: 99%
“…Based on observation that in PCL the response to standard therapy is extremely poor and the use of thalidomide in advanced MM has resulted in marked responses even in patients with advanced diseases, including those who relapsed after high-dose chemotherapy [69][70][71][72], some authors have used this promising drug also in patients with PCL [73,74]. Wohrer et al [75] reported the use of thalidomide in a patient with PPCL as a first line therapy achieving a very good partial response rapidly.…”
Section: Thalidomidementioning
confidence: 99%
“…Anagnostopoulos et al [19] reported the median OS of 38 months. Cibeira et al [20] reported PFS of 15.6 months and OS of 28.4 months among relapsing MM patients.…”
Section: Discussionmentioning
confidence: 99%